Cascaded switching supervisory control of nonlinear underwater robotic vehicle for pipeline tracking - Chin, Cheng Siong (2009)
In recent years, remotely operated vehicles (ROV) have experienced tremendous growth in underwater pipeline inspections where human diving is impractical. However, the ROV stabilization and pipeline tracking applications present several difficulties due to its inherent nonlinear state coupling, model uncertainties due to hydrodynamic forces, and in particular, and the vehicle possessing fewer actuators than the available degrees of freedom i.e. being underactuated. Most existing methods solve the problem in two-dimensional plane, very often by ignoring the nonlinear coupled terms and hydrodynamic uncertainties in the control system design, and treating stabilization and tracking separately.